Building Effective Justice Institutions: The Challenge Of Developing Competence Management Practices - de Sá Affonso da Costa, Isabel; Merz Fernandes de Souza, Karin; Távora Raunheitti, Vivian (Revista ADM.MADE, 2020)
The United Nations Sustainable Development Goals (SDG) provide a frame of reference for signatory countries to guide public policies and institutional strategies at all government levels. Building the institutions capable of delivering the SDG relies on well-designed organizational processes and people not only committed to the fulfilment of their duties, but also with the competences to deliver them. This paper is part of a research effort that aims to identify how Brazilian public institutions develop the competences of their employees in face of the limitations imposed by legal requirements, especially those stemming from the public examinations model. Specifically, the paper main objective was to identify managers and server"s perceptions about competence management in the institutions they work for. Considering the huge challenge represented by the delivery of justice for the achievement of the SDG, the study focus on Judicial Branch institutions. The research, carried out in 2019, was based on a sample of six public examinations that took place between 2013 and 2015. Data were collected through interviews with HR managers, questionnaires applied to sworn candidates in higher level Administration positions and also official reports and legislation of public examinations. Results show that managers reveal no in-depth knowledge about competence management and its impact in HR processes. This might ingrain an insufficient awareness and proactivity in the actions directed to the management of competences, as well as poor effectiveness of the actions carried out. The research concludes that the agencies commitment to strengthen their missions through competence management are still incipient.